Analisis Manajemen Perpustakaan Madrasah Aliyah Darul Ulum Di Kecamatan Ciracap Kabupaten Sukabumi - Muhidin Muhidin (JURNAL ILMIAH PENDIDIKAN KEBUDAYAAN DAN AGAMA, 2026)
Problems that occur in the MA Darul Ulum library in Ciracap district, Sukabumi regency include library staff who have not met educational qualifications, and inadequate infrastructure. The purpose of this study is to determine and describe the profile of the MA Darul Ulum library based on work planning, organizing, mobilizing, supervising, filling positions, empowerment, motivation, and facilities in the MA Darul Ulum library. This study uses a qualitative approach with a case study type. Data collection techniques include participant observation, interviews, and documentation studies. Data analysis in this study was carried out in three ways, namely data uncitation, data categorization, and data interpretation. Data validity testing was carried out by: 1) expanding participation; 2) persistence; 3) Triangulation; 4) peer review; adequacy of reference materials; 6) member checking; 7) audit for dependency criteria; and 8) audit for certainty criteria. The results of this study indicate that, several management function activities are based on eight elements in the theory of library management functions, librarian work planning includes monthly, short-term, and long-term. The organization is well-organized and structured. Mobilization includes service initiatives. Supervision includes circulation, serialization, and system supervision. Positions are filled through internal and external placements. Librarian empowerment is carried out through seminars and training. The head of the library motivates librarians to provide the best possible service. Facilities at the MA Darul Ulum library are not yet optimally functioning